Exploring The Effect of Discussion Based Learning in The Flipped Classroom on Physics Concept Mastery - Saputri, Mawarni; Evendi, Evendi; Jannah, Rouzatul (Jurnal Pendidikan MIPA, 2025)
This study aims to determine the effect of the Flipped Classroom learning model through the discussion method in improving students' conceptual understanding in physics learning. The population in this study consisted of all 49 eleventh-grade students, divided into a control class and an experimental class. The instruments used in this study were test instrument (two tier test) and non-test instruments (observation sheet and student response questionnaires). Students categorized as having a "known concept" in the control class increased to 67%, while in the experimental class, this increased to 88%. Students categorized as having a "misconception" in the control class decreased to 33%, and in the experimental class, this decreased to 20%. Students categorized as "guessing" in the control class decreased to 4%, while in the experimental class, this decreased to 0%. Students categorized as having an "unknown concept" in the control class decreased to 33%, while in the experimental class, this decreased to 24%. The results of the analysis of the student response questionnaire showed an average score of 72.25, which indicated to "good" category. The hypothesis test results revealed a ????????ount value of 5.605 > ???????????????????????? value of 1.67, indicating a significant difference in the improvement of conceptual understanding between students in the experimental and control class. Furthermore, the N-Gain analysis resulted in a score of 0.74, categorized as high. Therefore, it can be concluded that the Flipped classroom learning model through the discussion method positively influences students' conceptual understanding in physics learning.       Keywords: flipped classroom learning model, discussion method, conceptual understanding.